Teacher’s Compliment for Students and Its Impact on Their Interest in Learning English: A Case Study at the Second Grade of SMAN 7 Wajo - Nurul Aprianty; Baso Jabu; Geminastiti Sakkir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This study aims to find out how teachers give compliments to students when teaching English. This research used a qualitative descriptive method. The data collection in this study was carried out by observing the atmosphere in the classroom during the learning process and interviewing 6 students from SMAN 7 Wajo. The results of this study found that the teacher gives compliments to students verbally and non-verbally. For verbal compliment the teacher used words such as: